Evaluating the structural performance of masonry walls incorporating recycled plastic bricks under monotonic and cyclic loading - Moulai Arbi, Youcef; Mahmoudi, Noureddine; Bentahar, Mohammed (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose:This study evaluates the structural performance of masonry walls made from recycled plastic bricks under monotonic and cyclic loading. The purpose was to investigate the feasibility of using recycled plastic bricks as an alternative for masonry construction, focusing on their structural viability and potential environmental benefits. Methods:A simplified micro-modeling approach in Abaqus was employed to simulate the behavior of these walls. The plastic bricks were represented with solid elements, while the mortar joints were modeled through cohesive interactions. The numerical model underwent validation through a mesh sensitivity analysis and was subjected to vertical compression followed by horizontal loading. Results:The findings indicated a reduction in strength compared to traditional masonry materials. However, the study successfully captured the structural response and damage evolution of masonry walls under the specified loading conditions. Despite the reduced strength, the structural viability of recycled plastic bricks was strongly affirmed, and the behavior observed under load conditions was particularly informative. Conclusions:The investigation underscored the potential of plastic composite bricks in contributing to sustainable building practices. The outcomes validated the feasibility of incorporating plastic bricks into construction, highlighting their environmental benefits and sustainable implications. This study advanced the field of sustainable construction materials by demonstrating the practical application and benefits of using recycled plastic bricks.